Mechanical and durability of geopolymer concrete containing fibers and recycled aggregate - Mohamed, Abdelaziz Yousuf; Canpolat, Orhan; Al-Mashhadani, Mukhallad M. (TECHNO-PRESS, 2022)
Recently, the interminable ozone depletion and the global warming concerns has led to construction industries to seek for construction materials which are eco-friendly. Regarding this, Geopolymer Concrete (GPC) is getting great interest from researchers and scientists, since it can operate by-product waste to replace cement which can lead to the reduction of greenhouse gas emission through its production. Also, compared to ordinary concrete, geopolymer concrete belongs improved mechanical and durability properties. In spite of its positive properties, the practical use of geopolymer concrete is currently limited. This is primarily owing to the scarce structural, design and application knowledge. This study investigates the Mechanical and Durability of Geopolymer Concrete Containing Fibers and Recycled Aggregate. Mixtures of elastoplastic fiber reinforced geopolymer concrete with partial replacement of recycled coarse aggregate in different proportions of 10, 20, 30, and 40% with natural aggregate were fabricated. On the other hand, geopolymer concrete of 100% natural aggregate was prepared as a control specimen. To consider both strength and durability properties and to evaluate the combined effect of recycled coarse aggregate and elastoplastic fiber, an elastoplastic fiber with the ratio of 0.4% and 0.8% were incorporated. The highest compressive strength achieved was 35 MPa when the incorporation of recycled aggregates was 10% with the inclusion of 0.4% elastoplastic fiber. From the result, it was noticed that incorporation of 10% recycled aggregate with 0.8% of the elastoplastic fiber is the perfect combination that can give a GPC having enhanced tensile strength. When specimens exposed to freezing-thawing condition, the physical appearance, compressive strength, weight loss, and ultrasonic pulse velocity of the samples was investigated. In general, all specimens tested performed resistance to freezing thawing. the obtained results indicated that combination of recycled aggregate and elastoplastic fiber up to some extent could be achieved a geopolymer concrete that can replace conventional concrete.
Keywords: compressive strength; flexural strength; geopolymer concrete; recycled aggregate; FLY-ASH; STRENGTH; MICROSTRUCTURE; COMPOSITES; EXPOSURE; GGBS; Computer Science; Construction & Building Technology; Engineering; Materials Science